Changes in Diet Quality from Mid- to Late Life Are Associated with Cognitive Impairment in the Singapore Chinese Health Study. Issue 9 (28th May 2021) - Tong, Eunice Huiying; Lai, Jun S; Whitton, Clare; Neelakantan, Nithya; Zhou, Yanfeng; Chen, Cynthia; van Dam, Rob M; Feng, Lei; Pan, An; Chong, Mary Foong-Fong; Koh, Woon-Puay
ABSTRACT: Background: Although higher diet quality at mid-life has been associated with better cognitive function in late adulthood, it is unclear whether dietary improvement after mid-life may reduce the risk of cognitive impairment. Objectives: We examined associations between changes in diet quality and risk of cognitive impairment in the Singapore Chinese Health Study cohort. Methods: We used data from 14, 683 Chinese men and women who were recruited at ages 45 to 74 y from 1993 to 1998 and re-interviewed after 20 y at ages 61 to 96 y during follow-up 3 (2014–2016). Diet quality was measured using the Dietary Approaches to Stop Hypertension (DASH) scores at baseline and follow-up 3 interviews. Cognitive impairment was defined using scores from the Singapore-modified Mini-Mental State Examination at the follow-up 3 interview. Multivariable logistic regression models were used to estimate ORs and 95% CIs for the associations between change in DASH scores and cognitive impairment. Results: Higher quintiles in DASH scores at baseline and follow-up 3 interviews were associated with lower odds of cognitive impairment in a dose-dependent manner (both: P -trend < 0.001). Compared with participants with consistently low DASH scores, the OR (95% CI) of cognitive impairment was lowest, at 0.64 (0.51, 0.79), in those with consistently high DASH scores. Those with small (OR: 0.80, 95% CI: 0.65, 0.98) or moderate–large (OR: 0.72, 95% CI: 0.59, 0.86) increases in DASH scores were associated with significantly lower odds of cognitive impairment than those with consistently low DASH scores. Associations were consistent across subgroups by sex, BMI (kg/m 2 ; <23 or ≥23), and age (<60 y, ≥60 y) at baseline. Conclusions: Although maintaining high diet quality confers the lowest risk, improving diet quality from mid- to late life was still associated with a lower risk of cognitive impairment in late adulthood.